2012
DOI: 10.1111/j.1460-6984.2012.00177.x
|View full text |Cite
|
Sign up to set email alerts
|

The working practices and clinical experiences of paediatric speech and language therapists: a national UK survey

Abstract: Citation: Pring, T., Flood, E., Dodd, B. and Joffe, V. (2012). The working practices and clinical experiences of paediatric speech and language therapists: a national UK survey. International Journal of Language & Communication Disorders, 47(6), pp. 696-708. doi: 10.1111/j.1460-6984.2012 This is the unspecified version of the paper.This version of the publication may differ from the final published version. The working practices and clinical experiences of paediatric speech and language therapists: A national… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 16 publications
(16 reference statements)
2
36
0
1
Order By: Relevance
“…We have shown that the 0.6 OT staffing WTE per 10 beds is not sufficient to meet the needs of patients and resulted in patient-to-OT ratios that were spuriously high. However, the overall staffing pattern is consistent with the DH Survey of Stroke Unit Staffing and Patient Dependency [16] which reported that only 25% of units had adequate staff numbers for rehabilitation. Similarly, the Sentinel Audit [5] reports that "access to occupational therapy is slower for many patients than ideal" (p. 35).…”
Section: Discussionsupporting
confidence: 67%
“…We have shown that the 0.6 OT staffing WTE per 10 beds is not sufficient to meet the needs of patients and resulted in patient-to-OT ratios that were spuriously high. However, the overall staffing pattern is consistent with the DH Survey of Stroke Unit Staffing and Patient Dependency [16] which reported that only 25% of units had adequate staff numbers for rehabilitation. Similarly, the Sentinel Audit [5] reports that "access to occupational therapy is slower for many patients than ideal" (p. 35).…”
Section: Discussionsupporting
confidence: 67%
“…This study partially concurs with existing literature that suggests that SLTs prefer ‘direct’ intervention (Pring et al . ). It also corresponds with evidence from studies suggesting that SLTs expect parents to assume an observer or helper role (Sugden et al .…”
Section: Discussionmentioning
confidence: 97%
“…The growth in parent training (Pring et al . , Roulstone 2012) and parent–child interaction therapy (Falkus et al . , Klatte and Roulstone ) depends on parents assuming a learner role.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, we sought to overview the generic and condition-specific health-related quality of life (HRQoL) measures currently being used in the field, and whether any such measures were suitable for informing service delivery priorities within this population. Because health care needs among children with SaLD tend to be heterogeneous, with the focus being the child's specific needs (Pring, Flood, & Dodd, 2012), it has proven difficult to apply outcome measures in a consistent and systematic way across the population of children with SaLD.…”
Section: Introductionmentioning
confidence: 99%